Safety and efficacy of botulinum neurotoxin in the treatment of erectile dysfunction refractory to phosphodiesterase inhibitors: Results of a randomized controlled trial. (7th October 2021) - Abdelrahman, Islam Fathy Soliman; Raheem, Amr Abdel; Elkhiat, Yaser; Aburahma, Abdelrahman A.; Abdel‐Raheem, Tarek; Ghanem, Hussein
Abstract: Background: There has been recent interest in the use of botulinum neurotoxin (BoNT) in the field of Andrology, whereby it has been investigated in the treatment of penile retraction and premature ejaculation. Objectives: To evaluate the safety and efficacy of intracavernosal BoNT‐A injection in the treatment of patients with erectile dysfunction (ED) refractory to oral phosphodiesterase inhibitors (PDE5Is). Patients and methods: A double‐blind randomized placebo‐controlled prospective comparative study conducted at one center and involved 70 patients with ED refractory to PDE5Is. At baseline, the following data were collected: erection hardness score (EHS), peak systolic velocity (PSV), end diastolic velocity (EDV), sexual health inventory for men (SHIM), and the sexual encounter profile 2&3 (SEP‐2&3) questionnaires. Treatment group ( n = 35) received a single ICI of 100 units of BoNT‐A in 2 ml of saline and control group ( n = 35) received a single ICI of 2 ml of saline. EHS, PSV, and EDV were assessed at 2 weeks post treatment. SHIM, SEP‐2, SEP‐3, and global assessment questionnaire (GAQ‐Q1&Q2) were completed at 2‐, 6‐, and 12‐weeks post treatment. Results: Two weeks post treatment, the treatment group showed a statistically significant improvement in the mean EHS, PSV, EDV, and GAQ‐Q1 positive responders ( p < 0.001) compared to the control group. At 6‐ and 12‐weeks post treatment, the treatment group showed a statistically significant improvement in the SHIM scores, SEP‐2, and GAQ‐Q1&Q2 positive responders compared to the control group. At 6 weeks, where there was a 5‐point improvement in the mean SHIM score of the treatment group (10±5.9 from 5.4±1.7 at baseline) versus no improvement in the placebo group, 18 patients in the treatment group (53%) were able to have an erection hard enough for vaginal penetration versus only one patient in the control group. Conclusion: BoNT‐A is safe and effective as a potential treatment for ED refractory to PDE5I therapy.